PEDAGOGICAL TECHNOLOGY AIMED AT STUDENTS’ ADAPTATION TO DISCIPLINE-BASED EDUCATION IN SECONDARY SCHOOLS - Ekaterina M. Cheprakova; Alexander A. Frolov (Obrazovanie i Nauka)
The aim of the study is to describe the educational technology aimed at students adaptation to discipline-based education in basic school; results discussion of the application practice to the educational process of the 5th grade.Methods. The methods involve learning experience, school documentation analysis, pedagogical experiment, study of students’ creativity and pedagogical experience on its organizational work. Systematic approach is used while structuring of the 5th grade students’ representations on the disciplines’ content of primary and basic general education on the methodological levelResults. The pedagogical technology of breaking the students’ educational disadaptation in the basic school is presented. The program of the course «All the subjects are good» is worked out. This program may allow students to adapt to the discipline content of the general education, to understand the essence of curriculum disciplines content and links between them, and the motivation development towards disciplinebased education evidence students’ adaptation. These objectives can be achieved through generation of skills based on the algorithmic of the concepts’ definitions mastering. The pilot implementation of the proposed technology in secondary school № 65 and in the Center «Giftedness and technology» of Yekaterinburg is presented.Scientific novelty. The effective way of neutralization and elimination of students’ discipline-educational disadaptation based on purposeful development of their conceptual thinking is proposed.Practical significance. The technology developed by authors allows teachers to form and develop the universal educational actions representing itself as a result of school training in the requirements of the educational standard. Timely use of this technology at transition age of children from primary school to secondary one provides the further success of their education.